PENGARUH MEDIA PEMBELAJARAN E-LEARNING, KREATIVITAS DOSEN TERHADAP MOTIVASI BELAJAR DAN HASIL BELAJAR MAHASISWA PENDIDIKAN ADMINISTRASI PERKANTORAN STAMBUK 2021 FAKULTAS EKONOMI UNIVERSITAS NEGERI MEDAN - Enda Claudia Layasina Br Pinem; Hasyim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of e-learning learning media and lecturer creativity on students’ learning motivation and learning outcomes of students in the Office Administration Education Study Program, Class of 2021, Faculty of Economics, Universitas Negeri Medan. This research used a quantitative approach with an ex post facto method. The population consisted of 89 student an all were seleted as research samples using the total sampling technique. Data were collected using questionnaires with a Likert scala that had been tested for validity an realibilty. Data analysis was conducted using multiple linear regression analysis with SPSS software. The results showed that partially E-Learning learning media had a positive and significant effect on learning motivation with t value 5,200 > t table 1,988 and significance 0,000 < 0,05, while lecturer creativity also had a positive ang significant effect on learning motivation with t value 8,019 > t table 1,988. Furthermore, E-Learning learning media had positive and significat effect on learning outcomes with t value 6,098 t table 1,988, and lecturer creativity had positive and significant effect on learning outcomes with t value 5,474. T table 1,988. Simultaneously, E-Learning learning media and lecturer creativity significantly influenced learning motivation with F value 97,870 > F table 3,10, and learning outcomes with F value 21,834 > F table 3,10. The coefficient of determinaton indicated that the independent variables contributed 69,5% to learning motivation and 40,7% to learning outcomes. It can be concluded that E-Learning learning media and lecturer creativity have a positive and significant influence on student’s learning motivation and learning outcomes.